c-CBL/LCK/c-JUN/ETS1/CD28 axis restrains childhood asthma by suppressing Th2 differentiation - Nan Yang; Tianyue Wang (BMC, 2024)
Abstract Background Asthma is a common immune disease with high morbidity in children. Type 2 inflammation is the center of asthma development, and mainly mediated by a subset of CD4 + T cells, T helper 2 (Th2) cells. Excess Th2 differentiation was generally associated with asthmatic attack. Casitas B-lineage lymphoma (c-CBL) was reported to involved in T cell development and databank showed its decreased expression in CD4 + T cells from peripheral blood of asthmatic children. This study aims to investigate the role of c-CBL in childhood asthma and Th2 differentiation, and explore the underlying mechanism. Methods We collected peripheral blood samples from clinical childhood asthma cases and healthy controls, and determined c-CBL expression in CD4 + T cells. Asthma was induced in neonatal mice by ovalbumin (OVA) intraperitoneal injection and aerosol inhalation, and c-CBL expression in CD4 + T cells from peripheral blood and spleen was measured. Gain-of-function experiments was performed to confirm the effects of c-CBL on Th2 differentiation in vitro. Finally, c-CBL was delivered into asthmatic mice via lentivirus infection to verify its effects on experimental asthma. Results c-CBL was lowly expressed in CD4 + T cells from asthmatic children than those of healthy controls. Similarly, it was downregulated in CD4 + T cells from peripheral blood and spleen of asthma mice. Overexpression of c-CBL restrained lung pathological injury and type 2 inflammation in experimental asthmatic mice. Gain-of-function experiments demonstrated that c-CBL inhibited Th2 differentiation of CD4 + T cells from healthy children, and mediated the ubiquitination of lymphocyte cell-specific protein-tyrosine kinase (LCK). LCK acted as a kinase to phosphorylate and activate c-JUN, which was predicted to bind promoter sequence of CD28 by bioinformatic analysis. Dual-luciferase reporter assay verified that c-JUN and ETS1 synergically enhanced transcription of CD28, and this transcription activation was aggravated by LCK overexpression. Conclusion c-CBL alleviated asthma and suppressed Th2 differentiation by facilitating LCK ubiquitination, interrupting c-JUN activation and CD28 expression in vivo and in vitro. c-CBL/LCK/c-JUN/ETS1/CD28 axis was partially involved in childhood asthma, and may provide novel insights for clinical treatment for asthma.